Simple discrimination of sub-cycling cells by propidium iodide flow cytometric assay in Jurkat cell samples with extensive DNA fragmentation. Issue 6 (19th March 2018) - Babes, Ramona Madalina; Tofolean, Ioana Teodora; Sandu, Roxana Gabriela; Baran, Oana Elena; Cosoreanu, Vlad; Ilie, Maria Teodora; Duta, Alexandru Ionut; Ceausescu, Maria Catalina; Ciucur, Paul Mihai; Costache, Simona; Ganea, Constanta; Baran, Irina
ABSTRACT: Human leukemia Jurkat T cells were analyzed for apoptosis and cell cycle by flow cytometry, using the Annexin V/propidium iodide (PI) standard assay, and a simple PI staining in Triton X-100/digitonin-enriched PI/RNase buffer, respectively. Cells treated with doxorubicin or menadione displayed a very strong correlation between the apoptotic cell fraction measured by the Annexin V/PI assay, and the weight of a secondary cell population that emerged on the forward scatter (FS)/PI plot, as well as on the side scatter (SS)/PI and FL1/PI plots generated from parallel cell cycle recordings. In both cases, the Pearson correlation coefficients were >0.99. In cell cycle determinations, PI fluorescence was detected on FL3 (620/30 nm), and control samples exhibited the expected linear dependence of FL3 on FL1 (525/40 nm) signals. However, increasing doses of doxorubicin or menadione generated a growing subpopulation of cells displaying a definite right-shift on the FS/FL3, SS/FL3 and FL1/FL3 plots, as well as decreased PI fluorescence, indicative of ongoing fragmentation and loss of nuclear DNA. By gating on these events, the resulting fraction of presumably sub-cycling cells (i.e. cells with cleaved DNA, counting sub-G0 /G1, sub-S and sub-G2 /M cells altogether) was closely similar to the apoptotic rate assessed by Annexin V/PI labeling. Taken together, these findings suggest a possible way to recognize the entire population of cells undergoing apoptotic DNA cleavage and simultaneously determine the cell cycle distribution of non-apoptotic cells in PI-labeled cell samples with various degrees of DNA fragmentation, using a simple and reproducible multiparametric analysis of flow cytometric recordings.